The obscure nature of signature pedagogy in social work education: a Canadian perspective. Issue 3 (3rd April 2021) - Archer-Kuhn, Beth; Allen, Devin; Schweizer, Liz; Meghji, Faaria; Taiwo, Akin
ABSTRACT: Signature Pedagogy in social work education has been well discussed in the American context, yet, less so in Canada. In the United States, field education has been proclaimed as the signature pedagogy for social work in 2008 and reaffirmed in 2015. To date, the Canadian Association for Social Work Education (CASWE), has affirmed field education as a cornerstone of social work education, yet has not declared it as its signature pedagogy. The claim that all professions have a signature pedagogy piqued our curiosity about our Canadian position. This mixed methods study reflects the voices of three stakeholder groups in Western Canada. Focus groups were utilized to explore social work students, field education staff, and faculty members' understandings of social work signature pedagogy, and inform an on-line national survey of faculty and field education staff. Utilizing thematic analysis and descriptive statistics, the findings suggest common and disparate views between participant groups. Despite nuances in understanding, strong suggestions by some scholars, and some support for the value of defining signature pedagogy, there is not yet agreement on signature pedagogy in Canadian social work education.